Tribological Studies of Brake Pad Materials: Effect of Contact Pressure, Sliding Speed, and Relative Humidity - Lubis, Abdul Munir Hidayat Syah Lubis (2009)
A study on the friction and wear properties of brake pad materials under nominal contact pressure, sliding speed and relative humidity was carried out in order to understand the phenomena related to friction and wear processes at the contact surface of brake pad. Three LRT brake pads were employed and their compositions were examined using three x-ray techniques; (i) energy dispersive x-ray (EDX), (iii) x-ray fluorescence (XRF) and (iii) x-ray diffraction (XRD). The friction and wear studies were carried out using a three pins-on-disc apparatus over wide ranges of contact pressure, sliding speed and relative humidity. The worn surface morphology was examined by electron scanning microscopy and x-ray analysis. The results of friction curve analysis shows that friction took place by several stages and form six friction curve shapes, where each curve was influenced by the test parameters. The test parameters were also found influencing the duration of the friction stage. This phenomenon is affected by composition and thermal degradation of the samples. The appearance of friction curve shape also considered to be related to formation and destruction of friction layer process on the contact surface. X-Ray analysis of the friction layer at the mating surface indicated that the friction layer mostly consist of iron oxides. Wear of the sample show increasing wear with contact pressure and sliding speed. This factor is concluded due to increasing of plastic deformation, frictional heating and fatigue effect. Only wear of Pad-3 was found increase with relative humidity. This difference is considered affected by hardness, porosity and thermal degradation of the sample. Friction curve analysis and micrograph of wear debris indicated that wear process of the sample was taken place by three modes: (i) surface fracture, (ii) abrasion by wear debris and hard particles, and (iii) material transfer. The micrograph of the worn surface show that wear of the sample was taken place by combination of four mechanisms: (i) adhesion, (ii) abrasion, (iii) fatigue, and (iv) delamination